Кургани поблизу Заруддя і Горбанів у межиріччі Псла та Кривої Руди - Супруненко, О.Б.; Шерстюк, В.В. (Археологічні дослідження в Україні, 2010)
At the territory of Haleshchyna ferrous quartzites deposit between Zaruddya village of Kremenchuk Region and Horbani village of Kozelshchyna Region in Poltava Oblast, between the Ruda, Kryva Ruda and Psel Rivers flows the research of two ploughed barrows of the group II was conducted. A grave of Yamna culture period and eight graves of Zrubna culture period, two Scythian undercut graves ruined by the robbers, and a nomads’ sunk in tomb of the Golden Horde epoch were discovered.